Age of the Yarrabee and accessory tuffs: implications for the upper Permian sediment-accumulation rates across the Bowen Basin. Issue 7 (2nd October 2016) - Ayaz, S. A.; Martin, M.; Esterle, J.; Amelin, Y.; Nicoll, R. S.
ABSTRACT: The Yarrabee Tuff is a stratigraphically significant marker across the Bowen Basin separating the Fort Cooper–Burngrove–Fair Hill formations from the overlying Rangal and equivalent coal measures. At least three to four persistent tuffs (referred here as accessary tuffs) beneath the Yarrabee Tuff were recognised in the Fort Cooper Coal Measures as suitable for regional stratigraphic correlations. In this study, we determined the ages of the Yarrabee and accessary tuffs across different morphotectonic zones of the basin through high-precision U–Pb dating of zircon with the CA-IDTIMS technique. The age of the Yarrabee Tuff is found to be 252.69 ± 0.16 Ma in the Duckworth 11 well, 253.07 ± 0.22 Ma in the Crocker Gully 2 well and <252.58 ± 0.23 Ma in the Peat 1 well. The age range of the Yarrabee Tuff coincides with the previously published date of the Kaloola Tuff Member in Meeleebee 5 suggesting that the tuffs are stratigraphically equivalent. The age range for the accessory tuff 1 is 253.12 ± 0.12 Ma to 252.85 ± 0.16 Ma, 253.45 ± 0.08 Ma for accessory tuff 2 and 253.77 ± 0.17 Ma to 253.57± 0.18 Ma for accessory tuff 3, placing them in the upper Changhsingian Stage. The age of the accessory tuff 6 (less laterally consistent in the basin) from the Fair Hill Formation is 254.03 ± 0.03 Ma, placing it in the lower Changhsingian Stage. The age-constrained intervals allow the estimation of sedimentation rates using decompacted coal and clastic sediment thickness. In the Taroom Trough, the temporal variation in sedimentation rates is found to be 902 m/Ma in the Fair Hill Formation decreasing to 234.5 m/Ma in the overlying Burngrove Formation, reflecting a decrease in accommodation or sediment supply upwards in the sequence. Across the basin, the sedimentation rates for the Burngrove Formation are consistently higher in the Taroom Trough ranging between 234.5 and 224.5 m/Ma and lower rates of 112 m/Ma in the Roma Shelf. This regional variation reflects areas of high sedimentation rates that are high accommodation sites recognised by split coal seams and increased interburden. Conversely, low sedimentation rates reflect low accommodation sites, such as the Roma Shelf and the Burunga Anticline that are characterised by coalesced coal seams. The results help to understand stratal relationships across variable accommodation sites, basin-fill history of the basin including extent of sediment supply and paleotopographic controls during the evolution of the Bowen Basin. We also discuss criteria for interpreting the results of CA-IDTIMS U–Pb dating and consider the possible geological uncertainties related to either the primary magmatic processes or secondary reworking of tuffs at the site of deposition.